Anti-anxiety Effect of Aqueous and Ethanolic Extracts of Salvia leriifolia Benth. Leaves in Mice Using Elevated Plus Maze - H Hosseinzadeh; A Danaee; T Ziaee (Institue of Medicinal Plants, ACECR, 2008)
Background: Salvia leriifolia (Lamiaceae) is indigenous to the east of Iran and some part of Afghanestan. It has many pharmacological effects such as antinociceptive, anti-inflammatory, anti-ischemic, anti-hyperglycemic, hypnotic, muscle relexant, anti-peptic ulcer and anticonvulsant effects. Objective: In this research, the antianxiety effects of aqueous and ethanolic extracts of S. leriifolia Benth. leaves were studied using elevated plus maze. Method: Nine groups of male mice were used, each of which contained 7-10 animals. Half an hour before anti-anxiety test, the aqueous or ethanolic extracts (100, 200 and 400 mg/kg), diazepam (1 mg/kg) and saline were injected intraperitoneally to mice. The aqueous and ethanolic extracts were dissolved in saline or tween 80, respectively. In anti-anxiety test, the number of entries into open and closed arms by animals was recorded. In motor coordination (Rotarod test) experiment, the extracts were injected 30 or 60 min before the test and in locomotor activity (open field test) experiment, the extracts were injected 60 min before test. Results: In anti - anxiety test, among different doses of the aqueous or ethanolic extracts, only ethanolic extract (in dose of 100 and 200 mg/kg) significantly increased opened arms entrance (p<0.01) and all doses of the ethanolic and aqueous extracts declined closed arms entrance, dose dependently (p<0.001). In Rotarod and open field tests all of doses significantly decreased mice locomotion activity and motor balance (p<0.001). Conclusion: The ethanolic extract of S. leriifolia leaves extract showed anti-anxiety activity and declined locomotion activity and motor coordination in mice.